Yaw control torque generation for a hovering robotic hummingbird. (9th January 2019) - Roshanbin, Ali; Preumont, André
This study describes the design, development, and flight tests of a novel control mechanism to generate yaw control torque of a hovering robotic hummingbird (known as Colibri). The proposed method generates yaw torque by modifying the wing kinematics while minimizing its influence on roll and pitch torques. To achieve this, two different architectures of series and parallel mechanisms are investigated; they are mathematically analyzed to investigate their behavior with respect to cross-coupling effects. The analysis is verified by measuring the control torque characteristics. The efficacy of the proposed method is also explored by flight experiments.